1983
DOI: 10.1163/002829684x00038
|View full text |Cite
|
Sign up to set email alerts
|

Host Quality Effects On Sex Ratio of the Parasitic Wasp Anisopteromalus Calandrae (Chalcidoidea, Pteromalidae)

Abstract: The pteromalid wasp Anisopteromalus calandrae (Howard) is a parasite of larval instars of several species of beetles. In our experiments we used larvae of the granary weevil (Sitophilus granarius L.) as hosts. Host size may differ considerably, older larvae being much larger than younger ones. Fitness of the wasps' offspring depends on host size but differences between small and large sons are probably less than between small and large daughters. A number of experiments were carried out to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
0
13
1
1
Order By: Relevance
“…The progeny sex ratio (male/total) on small hosts was 1.00 (one of one), 1.00 (eight of eight), and 0.83 (®ve of six) when they had experienced with no host, parasitized host and healthy host, respectively. The ratio on small hosts seemed to be higher than that reported by other authors (VAN DEN ASSEM et al, 1984). However, we obtained only a few adults emerged on the small hosts (six adults) and the higher sex ratio could hardly have any statistical signi®cance.…”
Section: Host Size and Progeny Sex Ratiocontrasting
confidence: 92%
See 1 more Smart Citation
“…The progeny sex ratio (male/total) on small hosts was 1.00 (one of one), 1.00 (eight of eight), and 0.83 (®ve of six) when they had experienced with no host, parasitized host and healthy host, respectively. The ratio on small hosts seemed to be higher than that reported by other authors (VAN DEN ASSEM et al, 1984). However, we obtained only a few adults emerged on the small hosts (six adults) and the higher sex ratio could hardly have any statistical signi®cance.…”
Section: Host Size and Progeny Sex Ratiocontrasting
confidence: 92%
“…The preference of female A. calandrae for large hosts might lead the host population to be dominated by young hosts (small host), which might, in turn, cause the population sex ratio to be male biased. However, this explanation is not consistent with the fact that progeny sex ratio of A. calandrae was female biased except when the age distribution of the host was extremely biased to the young larvae (£ 3rd instar) ( VAN DEN ASSEM et al, 1984); a situation that is unlikely to occur in the host±parasitoid system.…”
Section: Introductionmentioning
confidence: 89%
“…This suggested that E. nacheri females changed their oviposition strategy in response to their encounters with hosts. Although observations that previous experience affected offspring sex-ratio have been reported for several parasitic wasps (Cloutier et al 1991;van den Assem et al 1984), the saturated sex ratios were different from those of the host aphid species. When M. persicae was supplied as the host, the offspring sex-ratios asymptotically approached 0.5-0.6.…”
Section: Discussionmentioning
confidence: 61%
“…O aumento do tempo de exposição dificulta a visualização dos efeitos do superparasitismo, devido à ação exploratória e randômica das fêmeas adultas sobre os hospedeiros (Cardoso & Milward-de-Azevedo 1995). Outros fatores também podem influenciar na razão sexual de vespas parasitóides, como o tamanho do hospedeiro, onde os mais robustos apresentam uma tendência a um maior número de fêmeas na prole como verificado por Van den Assem et al (1984) para Anisopteromalus calandrae (Howard) (Chalcidoidae, Pteromalidae). Shuker et al (2005) testaram uma hipótese chamada Asymetrical Local mate competition, que é a extensão da teoria de Hamilton (1967), Local mate competition (LMC), que sustenta a tendência ao aumento da taxa de fêmeas na prole de espécies onde apenas as fêmeas abandonam o pupário dispersando-se.…”
Section: Discussionunclassified